Data Supporting "Managing Assumption-Driven Design Change via Margin Allocation and Trade-offs" - Chen, Xin; El Fassi, Soufiane; Riaz, Atif; Guenov, Marin; van Heerden, Albert S. J.; Jimeno Altelarrea, Sergio (Cranfield University, 2023)
Results of design of experiment study produced in "Managing Assumption-Driven Design Change via Margin Allocation and Trade-offs". Presented as Figures 16, 17, and 18 in the paper.
Keywords: Aircraft design'; 'Margin Management'; 'Assumption Management'; 'Design Trade-offs'